Dynamic and frequency behaviour of the MARFE instability on FTU. (August 2017) - Mazzotta, C.; Spizzo, G.; Pucella, G.; Giovannozzi, E.; Tudisco, O.; Apruzzese, G.; Bin, W.; Esposito, B.; ,
Highlights: The dependence of the principal frequency of the MARFE instability versus basic plasma parameters is investigated. A study of the ion drift on the MARFE instability has been performed. The MARFE localization with respect to the ion drift direction, which can influence the stable and unstable positions, is discussed. Abstract: The Frascati Tokamak Upgrade (FTU) device can operate at high electron density regimes of the order of 10 20  m − 3, where the MARFE instability is present at various plasma current and magnetic field values. When the MARFE is well developed and oscillating, its movement causes continuous density fluctuation, contaminating the integral density measurements. The amplitude and frequency of these density fluctuations are well revealed by the high resolution interferometer available on FTU, the dependence of the frequency versus basic plasma parameters is investigated in this paper. A specific experimental session on FTU, including some discharges with reversed toroidal magnetic field, and pushing the plasma column towards the internal or external side of the vacuum chamber, respectively, has shown that, when the plasma column is distant from the toroidal limiter, the MARFE is stable and does not oscillate around the mid plane. For these last cases the MARFE localization with respect to the ion drift direction, which can influence the stable and unstable positions, is also discussed.